(untitled) (Biological Sciences - PJSIR, 1999)
to develop a rather rapid, precise and sensitive method for the determination of valuable minor and trace metals in sulphide minerals using flame atomic absorption spectrophotometer. Moreover, the present studies are continuation of our earlier investigations (Siddiqi et at 1984; Naeem et at 1988; Khan et at 1990) regarding geochemical evaluation of and sphalarite of Kohistan-Hazara and the copper ore deposits of North Waziristan Agency (North West Frontier Province of Pakistan).